Trading for peace. (12th July 2018) - Jha, Saumitra
Abstract: I examine the conditions under which trade can support peaceful coexistence and prosperity when particular social and ethnic groups are cheap targets of violence. A simple theoretical framework reveals that for a broad set of cases, while inter-group competition generates incentives for violence, the presence of non-replicable, non-expropriable inter-group complementarities becomes necessary to sustain peaceful coexistence over long time horizons. In addition to complementarity, two further conditions are important for deterring violence over time. When relatively mobile groups (e.g. immigrants) are vulnerable, a credible threat to leave can deter violence. When less mobile (indigenous) groups are vulnerable, high-monitoring costs that allow them to withhold production can improve their gains from trade. I describe the implications for indigenous entrepreneurship and cultural assimilation, the development of local institutions supporting inter-ethnic trust and immigration policies and policies aimed at mitigating conflict through financial innovations. I illustrate these implications using contemporary evidence and historical cases of organizations and institutions created to engender trade and support peace drawn from Africa, Asia, Europe and Latin America.